KAJIAN ETNOBOTANI TUMBUHAN PANGAN PADA MASYARAKAT SUKU SEKO DI DESA TANAH HARAPAN KECAMATAN PALOLO KABUPATEN SIGI SULAWESI TENGAH - Bill Yorsan Yonathan; I Nengah Suwastika; Ramadhanil Pitopang (Biology Department, Mathematics and natural science, Tadulako University, 2016)
A research entitled “Ethnobotanical Study of food Plant in the Seko ethnic group in Tanah Harapan Village, Sigi Regency, District Central Sulawesi” has been carried out from March to April 2015. The research objective was to obtain the information of Plant diversity, part of the plant used as food and how to use as food. The research was done by methods that is using interview technique to 40 respondents with quisioner sheet. The result showed that there were fifty five (55) plants species that used by the Seko ethnic group in Tanah Harapan Village. The highest percentage that used in the part of plants were 40% of fruit. The Seko ethnic group in Tanah Harapan village utilize plants as food in a way that it can be consumed directly or to go through the first processing is cooked, boiled, fried, baked and coconut milk added. Key word : Seko Ethnic, Tanah Harapan Village, Sigi Central Sulawesi, Ethnobotanical Food Plant.